2018
DOI: 10.1177/0898756418774575
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Transformation of a Canine Papillomavirus Type 1-Induced Persistent Oral Papilloma in a 3-Year-Old Dog

Abstract: This case report describes a rare case of a persistent canine papillomavirus type 1 (CPV-1)-induced oral papilloma that underwent malignant transformation into an oral squamous cell carcinoma (OSCC) in a 3-year-old Labrador retriever cross. Initially, the patient had multiple and multifocal verrucous lesions populating the oral cavity exclusively. The papillomas persisted despite multiple surgical ablations, azithromycin, interferon α-2b, alternative medicines, and off-label drug use of an immunostimulant. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 76 publications
(280 reference statements)
2
26
0
Order By: Relevance
“…Several retrospective studies based on molecular or serological survey evidence have declared that CPV 1 is unlikely to bring about malignant changes [49][50][51]. Controversially, accumulative studies have revealed the identification of CPV 1 in SCCs [26,27]. Furthermore, CPV 2 was also only identified in a benign viral papilloma case in the present study.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…Several retrospective studies based on molecular or serological survey evidence have declared that CPV 1 is unlikely to bring about malignant changes [49][50][51]. Controversially, accumulative studies have revealed the identification of CPV 1 in SCCs [26,27]. Furthermore, CPV 2 was also only identified in a benign viral papilloma case in the present study.…”
Section: Discussionsupporting
confidence: 44%
“…As for the canine PVs, CPV 1, 2, 3, 7, 12, 16, and 17 have been speculated to cause malignant transformation of the epithelium [1,28]. The association of viral antigens or genome with malignant lesions has also been demonstrated in CPV 1-, 2-, 12-, and 16-infected animals [26,27,29,33]. In the present study, we examined canine papillomas and canine SCCs taken from the oral cavity including the gingiva, lip, and tongue and demonstrated CPV 1 in four benign lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that the use of an in-line suction as an appropriate smoke evacuation system and the potential aggressive freezing via cryotherapy intervention post-laser negated the risk of laser plume induced spreading of the viral disease. There is a report of a CPV-1-induced persistent oral papilloma that underwent malignant transformation into an oral squamous cell carcinoma 16. The possibility of a malignant transformation suggests using a more aggressive approach in extensive and persistent oral CPV growths as described in this case report.…”
Section: Discussionmentioning
confidence: 68%